PENERAPAN STRATEGI PEMBELAJARAN RECONNECTING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI KELAS XI TBSM SMKN 1 KUANTAN HILIR - Elwina Rosa; Sopiatun Nahwiyah; Alhairi Alhairi (Universitas Islam Kuantan Singingi, 2022)
This research of background lowly its his result of student learn at religion subject of islam ethic kindness and, low of him result of learning this student [is] caused by study strategy variation of teacher do not which is used by class. Therefore is, wrong of sau of[is way of to increase result of learning student that is passing applying of srategi study of reconnecting. Strategy study of reconnecting represent a[n study strategy by connecting again study which have been studied with study in this time. As for intention of this research that is to know do applying of reconnecting startegi can improve result learn student at religion subject of islam ethic kindness and in class of TBSM SMKN 1 Kuantan Hilir. this Type Research represent research of class action which is executed in 2 cycle. Subjek of this research is class of XI TBSM SMKN 1 Kuantan Hilir, data collecting technique that is by using observation, interview, and documentation of tes . While technique analyse data that is using percentage formula. As for result of research that is at final tes of cycle of I that is 46,67%, as according to complete criterion learn klasikal gone to school to be expressed complete if 85% complete student by klasikal. Therefore, can be concluded that complete learn klasikal at cycle of I not yet been reached by learn of cycle of II there are 12 complete student people with mean 79 and complete percentage of klasikal that is 86,67%. As according to complete criterion learn by klasikal expressed complete if 85% complete student by kalsikal. This matter have reached criterion which have been specified. Can be said that by study process by using strategy of reconnecting earn menigkatkan result of learning student.